The effect of Sargassum binderi alginate extract addition on the nutritional content of full cream Mung Bean Milk and its consumer acceptance - Rais Nur Latifah; Putri Rahmawati Az Zahro (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
Milk is one of the important nutritional components that consumed by children and adults. Mung Bean (Vigna radiata L.) contains high nutrition and functional compounds, as well as high nutrients content that the body needs. Mung Bean milk is processed into full cream Mung Bean milk with alginate addition. Variations of alginate addition are 1%, 1.5%, 2%, 2.5% and 3% (w/v). Characterization of full cream mung Bean milk is analysis of the viscosity, density, nutritional, total fiber content, and organoleptic analysis. Alginate is a heteropolysaccharide that has two monomers. The color of alginate is brown. The result of research in density and viscosity of the alginate are 1.43 g/mL and 7.42x10-3 kg m-1 s-1. The best composition for addition alginate to full cream Mung Bean milk is 3% (w/v). The result of the best full cream Mung Bean milk of carbohydrate, protein, fat, and total fiber content is 98 mg carbohydrates/mL milk; 0.97% in 5 mL milk; 0.32 mg fat/mL milk and 13.1 mg/mL milk. Organoleptic analysis of 3% (w/v) addition alginate in full cream Mung Bean milk is like category.©2021 JNSMR UIN Walisongo. All rights reserved.